Influence of non-collisional laser heating on the electron dynamics in dielectric materials. (3rd November 2016) - Barilleau, L; Duchateau, G; Chimier, B; Geoffroy, G; Tikhonchuk, V
Abstract: The electron dynamics in dielectric materials induced by intense femtosecond laser pulses is theoretically addressed. The laser driven temporal evolution of the energy distribution of electrons in the conduction band is described by a kinetic Boltzmann equation. In addition to the collisional processes for energy transfer such as electron–phonon–photon and electron–electron interactions, a non-collisional process for photon absorption in the conduction band is included. It relies on direct transitions between sub-bands of the conduction band through multiphoton absorption. This mechanism is shown to significantly contribute to the laser heating of conduction electrons for large enough laser intensities. It also increases the time required for the electron distribution to reach the equilibrium state as described by the Fermi–Dirac statistics. Quantitative results are provided for quartz irradiated by a femtosecond laser pulse with a wavelength of 800 nm and for intensities in the range of tens of TW cm −2, lower than the ablation threshold. The change in the energy deposition induced by this non-collisional heating process is expected to have a significant influence on the laser processing of dielectric materials.